The Philippine Higher Education Sector in the Time of COVID-19 - Joaquin, Jeremiah Joven B.; Biana, Hazel T.; Dacela, Mark Anthony (Frontiers in Education, 2020)
This paper reports the policy-responses of different Philippine higher education institutions (HEIs) to the novel coronavirus, COVD-19 pandemic. It compares these responses with those made by HEIs in Indonesia, Thailand, and Vietnam. Publicly-available data and news reports were used to gauge the general public’s reaction to these policies and how the Philippines’ responses fare with its Southeast Asian neighbours. The paper observes that despite the innovations made by Philippine HEIs in terms of alternative learning modes and technologies for delivering education, there are still gaps and challenges in their responses. It recommends that policy-responses and learning innovations should be grounded on a deeper understanding of distance education and should be sensitive to the call of the times.